A Survey of Intravenous Remifentanil Use for Labor Analgesia at Academic Medical Centers in the United States. Issue 5 (October 2017) - Aaronson, J.; Abramovitz, S.; Smiley, R.; Tangel, V.; Landau, R.
Abstract : (Abstracted from Anesth Analg, 124(4):1208–1210, 2017) Currently, there is no standardized protocol regarding the optimal administration, dosing strategy, and maternal monitoring requirements of intravenous (IV) remifentanil for labor analgesia. As this drug has the potential to cause sedation, respiratory depression, oxygen desaturation, and more, it is essential that clear recommendations be established.